Drivers of spatiotemporal variability in bycatch of a top marine predator: First evidence for the role of water turbidity in protected species bycatch. Issue 2 (24th December 2019) - Luck, Cian; Cronin, Michelle; Gosch, Martha; Healy, Kieran; Cosgrove, Ronan; Tully, Oliver; Rogan, Emer; Jessopp, Mark
Abstract: Bycatch of protected species in static net fisheries is a global conservation concern and is currently considered the dominant anthropogenic threat facing many marine mammal species. Effective bycatch mitigation remains challenging, contingent on an understanding of the underlying mechanisms that cause individuals to become entangled. We combined data collected by scientific observers and fishers to identify predictors of seal bycatch in static net fisheries along the west, southwest and south coasts of Ireland. We first analysed the broad regional and seasonal trends in seal bycatch before identifying environmental variables that could explain these patterns. Based on negative binomial generalized linear mixed effects models, seal bycatch significantly varied with season and decreased with greater distance to major seal colonies and in clearer, less turbid water. Synthesis and applications . Our results suggest that distance to major seal colonies was a significant driver of spatial variation in seal bycatch, and water turbidity a major driver of seasonal trends. These findings will enable us to identify future bycatch risk and target mitigation measures effectively. This is the first study to identify the effect of water turbidity on bycatch of a protected marine species. Increasing net visibility in turbid waters may provide a novel approach to mitigating against protected species bycatch in static net fisheries. Abstract : Our results suggest that distance to major seal colonies was a significant driver of spatial variation in seal bycatch, and water turbidity a major driver of seasonal trends. These findings will enable us to identify future bycatch risk and target mitigation measures effectively. This is the first study to identify the effect of water turbidity on bycatch of a protected marine species. Increasing net visibility in turbid waters may provide a novel approach to mitigating against protected species bycatch in static net fisheries.